2014
DOI: 10.1021/ie502338y
|View full text |Cite
|
Sign up to set email alerts
|

Alterable Superhydrophobic–Superhydrophilic Wettability of Fabric Substrates Decorated with Ion–TiO2 Coating via Ultraviolet Radiation

Abstract: To prepare a functional fiber surface with alterable superhydrophobic–superhydrophilic wettability on fabrics, a TiO2 hybrid sol was synthesized with tetrabutyl titanate and a fluoride silane coupling agent, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, via sol–gel technology. Within irradiation under UV light, the decay of the contact angle from superhydrophobicity to superhydrophilicity on the irradiated front fabric treated with the F–TiO2 hybrid sol was the fastest, and the contact angle on the irradiated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…The SEM image indicated that the surface of the cellulose fiber was rough, and there were abundant groove constructions and natural distortions (Figure 7(a)). 27 The roughness was increased after deposition, and the surface roughness of the modified fiber with DTES (Figure 7(b)) was lower than that of the fiber surface containing OTES (Figure 7(c)). The roughness distribution of the modified cellulose fiber was related to the water contact angle, and superhydrophobicity of the modified cellulose substrates containing OTES and DTES were remarkable.…”
Section: Properties Of Modified Cellulose Substratesmentioning
confidence: 96%
See 2 more Smart Citations
“…The SEM image indicated that the surface of the cellulose fiber was rough, and there were abundant groove constructions and natural distortions (Figure 7(a)). 27 The roughness was increased after deposition, and the surface roughness of the modified fiber with DTES (Figure 7(b)) was lower than that of the fiber surface containing OTES (Figure 7(c)). The roughness distribution of the modified cellulose fiber was related to the water contact angle, and superhydrophobicity of the modified cellulose substrates containing OTES and DTES were remarkable.…”
Section: Properties Of Modified Cellulose Substratesmentioning
confidence: 96%
“…Then the cellulose substrates were dried at 60 C for 20 min. 27 The dried cellulose substrates were uniformly irradiated under UV light with the Intelli-ray 600 UV lightbox produced by USA Uvitron Company (light intensity 50.0 mW/cm 2 , wavelength 253.7 nm) for 0-45 s to cure on the cellulose substrate (Figure 1).…”
Section: Cellulose Substrate Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5d, it was found that the paper surface can still achieve the transition between superhydrophobic and superhydrophilic after repeating the above soaking process 5 cycles, which showed that the reversible control of the wettability of the paper surface can be achieved by ion exchange between PF 6 − and Cl − . The concentration of the anion solution and the soaking time will have an important impact on the anion adsorption capacity of the polyelectrolyte molecular brush PMETAC, thereby affecting the contact angle of the paper surface [34,35]. The solvent used in this experiment was methanol.…”
Section: Analysis Of Surface Elements Of Modified Papermentioning
confidence: 99%
“…In recent years, many attempts have been made to endow cotton fabric with new functionalities, including antimicrobial activity, superhydrophobicity, and abrasion resistance . Various techniques, such as dip coating, solution immersion, sol‐gel coating, spray deposition, chemical vapor deposition, and graft polymerization have been tried to modify cotton surface. Because cotton fibers are generally soft and sensitive to abrasive forces, the improvement of wearing durability is of particular importance in clothing industry.…”
Section: Introductionmentioning
confidence: 99%